Gender Differences in Strategic Behavior in a Triadic Persecution Motor Game Identified Through an Observational Methodology - Pic, Miguel; Navarro-Adelantado, Vicente; Jonsson, Gudberg K. (Frontiers in Psychology, 2020)
The main objective of the work is to address the effective behavior of girls and boys through Triadic Motor Games (TMG). A chasing game “The Maze” was applied on two class groups with a total of 42 players, 18 girls, and 24 boys, who were 12- and 13-year-old secondary school students. An observational methodology was adopted, with a nomothetic, punctual, and multidimensional design. We used a mixed registry system that two expert observers later applied through an observational methodology, obtaining sufficient record-quality levels. THEME was applied to detect temporary regularities, while cross-tabulations and growth trees were applied with the SPSS v.24 tool to reveal whether girls and boys played in similar or distinct ways. The fact that the specific decision groups within the physical education class are different for girls and boys (p < 0.005) is worth reflecting on. The game’s TMG complexity was addressed through roles and subroles, giving rise to a certain motor asymmetry in relation to gender, which is an expression of behaviors lacking in playful neutrality. Through a mixed-methods approach, a study was built using observational methodology that reveals more varied motor solutions in girls, while male behavior showed greater specialization of roles and subroles, and the linkage of these solutions with the favorable modification of the marker. Identifying relevant variables when playing TMG allows a better understanding of girls and boys by analyzing their relationships, which are sometimes paradoxical, in a practical context.